Effects of 2.45 GHz Non-Ionizing Radiation on Anxiety-Like Behavior, Gene Expression, and Corticosterone Level in Male Rats: Long-term Radiation Exposure Modifies Memory and Anxiety Behavior in Rats - Tarsaei, Mahvash; Peyrovan, Zeinab Sadat; Mahdavi, Seyed Mohammad; Modarresi Chahardehi, Amir; Vafaie , Reza; Haidari, Mohammad Hosain (Journal of Lasers in Medical Sciences, 2022)
The effects of short-term and long-term exposures to 2.45 GHz radiofrequency electromagnetic radiation (RF-EMR) on anxiety-like behavior, corticosterone level, and gene expression were investigated. The animals have been classified into eight groups, sham groups and, exposed groups for short-term and long-term exposure to the same dose of RF-EMR for one hour daily. The Wi-Fi equipment in the sham control group was not turned on during the experiment. The goal of this study was to explore the effect of electromagnetic fields of 2.45 GHz on clinical signs such as bodyweight and anxiety-like behavior, including the elevated plus maze test and open-field test, and also on messenger RNA (mRNA) expression of Bax (Bcl2-associated x) and Bcl-2 (B-cell lymphoma 2) genes on the cognitive memory functions in an animal model of rats. Both genes were further confirmed by reverse transcriptase-polymerase chain reaction (RT-PCR). The semi-quantitative PCR method of electromagnetic fields in the 2.45 GHz range impacted the expression of Bax and Bcl-2 genes in the rat's memory. The present study exhibited that short-term radiation could decrease the percentage of entry into the open arm and the percentage of time spent, while there were no substantial impacts on the long-term radiation effect. Our data support the hypothesis that short-term exposure worked as a systemic stressor, raising plasma corticosterone and changing glucocorticoid receptor expression in the hippocampus. Additional research on this specific frequency and amount of radiation is required to discover strategies for protecting the nervous system from the detrimental effects of RF-EMR radiation.